Creación de una cafetería con servicio especializado de “auto-rápido - Dejo, Estefania (2009)
At first hour at the morning or to join your friends after a meal, there is no doubt that drinking a coffee is quite a pleasure. Now the market offers several opportunities that allow the people to meet in someplace and drink a delicious coffee. The difference in this coffee shop is that this service is only by drive-thru, so it is a quite different story. For many people this is a solution to save some time in order to be able to have a nice breakfast or a nutrition dinner. You can just stop by “Mi Tacita” and buy whatever you might need. It has always been, and will always be, about quality. We’re passionate about ethically sourcing the finest coffee beans, roasting them with great care, and improving the lives of people who grow them. We care deeply about all of this; our work is never done. We’re called partners, because it’s not just a job, it’s our passion. Together, we embrace diversity to create a place where each of us can be ourselves. We always treat each other with respect and dignity. And we hold each other to that standard. When we are fully engaged, we connect with, laugh with, and uplift the lives of our customers— even if just for a few moments. Sure, it starts with the promise of a perfectly made beverage, but our work goes far beyond that. It’s really about human connection.